Patterns of functional diversity of native and non‐native fish species in a neotropical floodplain. (12th May 2022) - Angulo‐Valencia, Mirtha A.; Dias, Rosa M.; Alves, Diego C.; Winemiller, Kirk O.; Agostinho, Angelo A.
Abstract: Human activities affecting freshwater ecosystems, such as regulation of rivers by dams and introduction of non‐native species, are recognised as major threats to freshwater biodiversity, with fish communities strongly impacted. We evaluated patterns of functional diversity of native and non‐native species in local fish assemblages in the upper Paraná River floodplain over a 33‐year period (1986–2019) in three rivers with different degrees of alteration by dams (highly altered, moderately altered, and little altered). We also examined the effect of non‐native species on functional diversity of native species and investigated the responses of functional traits of native and non‐native fishes in regions with different histories of flow alteration. We measured 13 functional traits associated with five niche dimensions: feeding, habitat use, metabolism, life history, and defence. Functional diversity was evaluated from functional richness, functional redundancy, and Rao's quadratic entropy. The effect of non‐native species on functional diversity indices of native species was evaluated using a simple linear regression between each index and the level of dominance by non‐native species. To evaluate changes in functional traits of native and non‐native species over time and among rivers, we performed an RLQ analysis. Functional richness and Rao's quadratic entropy of native species decreased over time, while functional redundance increased especially in the most altered river. The level of dominance by non‐native species was negatively associated with functional richness and Rao's quadratic entropy of native species. Native species that are migratory with high fecundity, single spawning events and large body size were most common during the first 2 decades and within the least altered river. Non‐native species with parental care, multiple spawning, relatively large eggs, and brood defence tended to have greater prevalence during the last 2 decades and within the moderately altered region. Comparison of temporal trends in the functional diversity and characteristics of native and non‐native fishes within regions of the upper Paraná River floodplain having different levels of environmental alteration suggests that non‐native species and alteration by dams interact to adversely impact the functional diversity of native fishes, with especially strong effects on migratory fishes with a periodic life history strategy.